Late outcomes of adult survivors of childhood non‐Hodgkin lymphoma: A report from the St. Jude Lifetime Cohort Study. Issue 6 (15th November 2016) - Ehrhardt, Matthew J.; Sandlund, John T.; Zhang, Nan; Liu, Wei; Ness, Kirsten K.; Bhakta, Nickhill; Chemaitilly, Wassim; Krull, Kevin R.; Brinkman, Tara M.; Crom, Deborah B.; Kun, Larry; Kaste, Sue C.; et al.
Abstract: Background: Survivors of childhood non‐Hodgkin lymphoma (NHL) are at increased risk for chronic health conditions. The objective of this study was to characterize health conditions, neurocognitive function, and physical performance among a clinically evaluated cohort of 200 childhood NHL survivors. Method: Chronic health and neurocognitive conditions were graded as per a modified version of the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE) and impaired physical function defined as performance < 10th percentile of normative data. Multivariable regression was used to investigate associations between sociodemographic characteristics, therapeutic exposures, and outcomes. Results: Survivors were a median age of 10 years (range 1–19) at diagnosis and 34 years (range 20–58) at evaluation. Eighty‐eight (44%) received radiation, 46 (23%) cranial radiation, and 69 (35%) high‐dose methotrexate. Most prevalent CTCAE Grades 3–4 (severe life‐threatening) conditions were obesity (35%), hypertension (9%), and impairment of executive function (13%), attention (9%), and memory (4%). Many had impaired strength (48%), flexibility (39%), muscular endurance (36%), and mobility (36%). Demographic and treatment‐related factors were associated with the development of individual chronic diseases and functional deficits. Conclusions: Clinical evaluation identified a high prevalence of chronic health conditions, neurocognitive deficits, and performance limitations in childhood NHL survivors.